Measurements of dielectron production in Au + Au collisions at √sNN = 27,39, and 62.4 GeV from the STAR experiment - Abdulhamid, Muhammad Ibrahim; Aboona, Bassam; Adamczyk, Leszek; Butterworth, Jonathan; Deppner, Ingo Martin; Herrmann, Norbert; Kisel, Ivan; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp; Zyzak, Maksym (Physical review, 2023)
We report systematic measurements of dielectron (e+e−) invariant-mass Mee spectra at midrapidity in Au+Au collisions at √sNN = 27, 39, and 62.4 GeV taken with the STAR detector at the Relativistic Heavy Ion Collider. For all energies studied, a significant excess yield of dielectrons is observed in the low-mass region (0.40<Mee<0.75 MeV/c2) compared to hadronic cocktail simulations at freeze-out. Models that include an in-medium broadening of the ρ-meson spectral function consistently describe the observed excess. In addition, we report acceptance-corrected dielectron-excess spectra for Au+Au collisions at midrapidity (|yee|< 1) in the 0-80% centrality bin for each collision energy. The integrated excess yields for 0.4<Mee<0.75GeV/c2, normalized by the charged particle multiplicity at midrapidity, are compared with previously published measurements for Au+Au at √sNN1 = 19.6 and 200 GeV. Models that include an in-medium broadening of the ρ-meson spectral function consistently describe the observed excess. The normalized excess yields in the low-mass region show no significant collision energy dependence. The data, however, are consistent with model calculations that demonstrate a modest energy dependence.
Gesehen am 26.02.2024
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, NN ist dabei tiefgestellt